(Lack of) Power and the Profession of Social Work - Wagner, Harald (Socialinė teorija, empirija, politika ir praktika, 2014)
SummaryThis paper deals with the question whether or not social work is a powerful player within the society. The perspective is a German one, but reflects the situation in the other European and Non-European countries. Its aim is to develop a multi-perspective model of understanding that in return can prove the situation in any country.In a first step the problem of power is related to a theory of symbolic generalised media. As according to Talcott Parsons, it is shown here that only a balanced combination of different media, like money, power and influence will lead to successful social actions. In a second step the reality of social fields after Pierre Bourdieu is focused. This helps to understand the importance of all players, resources and aims. Using the theory of communicative action of Jurgen Habermas it discusses what dimensions of social action are involved and how they relate to each other. And after stressing the possibilities of lobbying in the mass media, conclusions are formulated. So the article shows some of the biggest obstacles but also the possibilities for social work becoming a powerful player in post-modern societies.